Nilai Pendidikan Moral dalam Antologi Cerkak Wiring Kuning Karya Trinil - Kurnia, Frisma Arbiana Fitri (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2017)
Javanese society culture faded in the era of modernization is increasingly rapid due to the entry of other cultures and the growing loss of interest of young people in the culture of Java. Literature can be prose, poetry and drama. Cerkak is a literature that can provide life values such as education, morals, immoral etc. Cerkak as one of the alternative media of reading must be able to give positive things in it. That way, the reader is expected to apply the values that exist in cerkak for life. The data source from the literature work of Ã¢â‚¬Å“ AntologiCerkak Wiring KuningÃ¢â‚¬Â the use data collection techniques reading as a whole towards the of target literature and recording of the relevant data in a thorough. The result study of this study are expected to make the younger generation more able to understand the morality and value of education in the literature Antologi Cerkak Wiring Kuning.